2022
DOI: 10.1101/2022.05.21.22275421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the genetic diversity of SARS-CoV-2 genomes carrying the Omicron B.1.1.529 mutation

Abstract: In this work, we evaluated the levels of genetic diversity in 95 genomes of the carriers of the Omicron B.1.1.529 mutation in SARS-CoV-2 from South Africa, Asia, Massachusetts-USA, Rhode Island-USA, United Kingdom and Germany. All with 29,996pb extension and recovered from GENBANK and publicly available at the National Center for Biotechnology and Information (NCBI). All gaps and conserved sites were extracted for the construction of a phylogenetic tree and for specific methodologies of estimates of paired FST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…This present study found that there was high genetic diversity in the S gene. High genetic diversity in the S gene has also been reported in other studies [ 53 , 54 , 55 ]. The areas of high diversity indicate highly mutated genes.…”
Section: Discussionsupporting
confidence: 77%
“…This present study found that there was high genetic diversity in the S gene. High genetic diversity in the S gene has also been reported in other studies [ 53 , 54 , 55 ]. The areas of high diversity indicate highly mutated genes.…”
Section: Discussionsupporting
confidence: 77%